Being psychologically absent at work: Types and effects of job boredom. Issue 4 (13th June 2016) - Cole, Graham
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Addressing job boredom will be well down the list of priorities for most employers. Such indifference is ill-judged though. Damaging effects are likely and firms should be aware of that fact. Job boredom is often defined as a lack of interest in workplace tasks. Poor engagement guarantees that the employee involved will fail to properly utilize his or her capabilities. And since productivity takes an inevitable hit, the significance for companies is readily apparent. Practical implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent, information and presenting it in a condensed and easy-to-digest format